The Effect of Perceived Innovativeness on Interpersonal Adaptive Behavior and Service Offering Adaptive Behavior Mediated by Job Engagement Among Cafe Employees in Banda Aceh City - Yuliana Syaputri; Megawati Megawati; Lenny Rakhmawati; Nasrillah Nasrillah; Wirdah Irawati (Westscience Press, 2026)
This study aims to examine the effect of perceived innovativeness on interpersonal adaptive behavior and service offering adaptive behavior, with job engagement as a mediating variable, among cafe employees in Banda Aceh City. This study used a quantitative approach with Structural Equation Modeling (SEM) analysis techniques based on Partial Least Squares (PLS). Data were collected by distributing questionnaires to 110 respondents selected using purposive sampling techniques, with the criteria of being permanent employees who had worked at cafes in Banda Aceh City for at least six months. The results showed that perceived innovativeness had a positive and significant effect on interpersonal adaptive behavior and service offering adaptive behavior. However, job engagement was not proven to act as a mediating variable in this relationship. In other words, employees' perceived innovativeness directly influences their adaptive behavior without going through job engagement. These findings suggest that employees' perceived innovativeness plays a significant role in enhancing their adaptability, both in interpersonal interactions and in service offerings, regardless of their level of job engagement. This study provides practical implications for cafe management to create a work environment that supports innovation and job engagement to improve the quality of employee service adaptation.